Iron Oxide Nanoparticles: An Insight into their Biomedical Applications - Couto, Diana; Freitas, Marisa; Carvalho, Felix; Fernandes, Eduarda (Current Medicinal Chemistry, 2015)
Iron oxide nanoparticles (IONs) are among the most common types of nanoparticles (NPs) used in biomedical applications. IONs can be presented in different forms [e.g. magnetite (Fe3O4), hematite (α-Fe2O3) and maghemite (γ- Fe2O3)], and are usually coated with substances and/or polymers according to the purpose for which they are intended to be used. In recent years, IONs use has been increasing exponentially in many fields of biomedicine, namely in magnetic resonance imaging, cell sorting, tissue repair, induction of hyperthermia and drug delivery, among others. This review aims to provide an update on the different IONs and the substances and/or polymers that can be used to coat the IONs core as well as their applications and biological properties, namely their biodistribution in the human body and their cellular internalization pathways.
Keywords: internalization routes